Silver-based drugs in the treatment of inflammatory diseases of the nose - M. L. Derbeneva; A. L. Guseva (Медицинский совет, 2015)
The article describes the specific antibacterial, fungicidal and antiviral mechanisms of silver-based drugs and reasons for the demand for the group of drugs in the modern healthcare. The most widely used silver-based drugs, Collargol and Protargol, their use in the treatment of inflammatory diseases of the nose in clinical practice are discussed in detail.